Applying the Biopsychosocial Model in Resource-Limited Settings: A Mixed-Methods Study of Young Healthcare Professionals in Myanmar - Htet Lin Aung (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
The objective of this research is to assess the use of the biopsychosocial (BPS) model by young health care professionals in Myanmar. There is a need for further research examining how early-career providers cope with the traditional use of biomedicine and widespread cultural opposition to the BPS model in contexts of systemic resource shortages. The study employed a mixed-methods convergent design involving thirty-two health care professionals (aged 25–35), including physicians, nurses, and medical technicians. Data triangulation was achieved through structured surveys, semi-structured interviews, and field observations. Descriptive statistics were used to analyze quantitative data, while thematic analysis was applied to qualitative data to identify barriers to implementation. The survey results show that 53% of respondents consistently use the BPS framework in their clinical practice, whereas 47% reported infrequent use of the BPS model. Significant differences were observed across professions: 100% of physicians reported frequent use of the BPS model, compared with 46% of nurses and 43% of medical technicians. Qualitative findings revealed several barriers to the provision of holistic care, including acute resource shortages, insufficient discipline-specific training, and cultural resistance. Myanmar’s new health care workers are leading a shift toward biopsychosocial care rather than solely disease-specific care. Even in the presence of systemic barriers, these health care workers have shown that patient-centered or holistic care can be achieved in low-resource environments when supported by adequate institutional frameworks.